(untitled) (Anclajes, 2023)
The analysis of the cultural Cold War in Latin America has experienced a growing interest from disciplinary fields such as cultural history or literary studies. In this line of work, and with the aim of contributing to a transatlantic approach to the problem, the special issue “Cultural ties of socialist and transatlantic friendship: Latin American writers and the Eastern Bloc during the Cold War” emphasizes the study of the interrelationships between Latin American literature and various European socialist countries. For this, it attends to a corpus of a plural nature: from fictional texts or analysis of periodicals to, above all, non-fiction texts that authors of diverse origins (Argentina, Uruguay, Chile, Cuba or Mexico) produced after passing through nations located beyond the Iron Curtain.